Growth and stress of dourado cultivated in cages at different stocking densities - Braun, Neiva; Dafre, Alcir Luiz; Lima, Ronaldo Lima de; Beux, Luis Fernando; Brol, Fernanda Franciele; Nuñer, Alex Pires de Oliveira (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the growth and the stress levels of juvenile dourado (Salminus brasiliensis) cultivated in cages. Fish stocked at densities of 15 (D15) and 30 (D30) fish per square meter were evaluated in a completely randomized design with three replicates. Fish were fed twice a day with extruded ration (42% crude protein). Density influenced only biomass and daily food intake, and glucose and lactate concentrations increased over time. D15 and D30 did not influence the growth of dourado. However, the increase of glucose and lactate levels over time indicates that cultivation in cages is a stressful condition for this species.